DEVELOPMENT OF AUGMENTED REALITY PORTAL FOR MEDICININAL PLANTS INTRODUCTION - Permana, Rizki; Tosida, Eneng Tita; Suriansyah, Mohamad Iqbal (iora, 2022)
Augmented Reality Portal application of Human Herbal Medicinal Plants, it can be concluded that the AR portal application aims to visualize medicinal plants and as a means of knowledge and insight for the general public. That is by utilizing the sophistication of Augmented Reality Portal-based technology that can be accessed using an Android smartphone. The Augmented Reality Portal application of Medicinal Plants in the Insani Herbal Garden has been carried out in the trial phase, the results of the Structural Test show that the system is well structured, the results of the Functional Test show that every button on the system has functioned properly and the Validation Test includes distance testing with maximum results for objects to detect sound, which is 90 cm, slope trials with a distance of 90 cm, maximum results at 45 degrees with a time of 00.66 seconds, light level trials with object detection results faster when the sun is direct with time of 1 second, and testing the android specifications shows that the minimum operating system is android nougat 7.0 and supports AR Core.